Transformerless ultra-high gain buck-boost DC-DC converter with single-switch of reduced voltage stress - Cordeiro, Armando (2024)
This paper introduces a new DC-DC power converter topology capable of both step-up and step-down voltage conversion, with an exceptionally high voltage gain ratio.. Besides the high extension of the voltage gain range, the converter is also characterized by the use of a single switch. Moreover, the stress imposed on the switch's voltage is minimized, enabling the utilization of low-voltage, low RDS-ON MOSFETs. Consequently, this modification leads to reduced costs and losses associated with switch conduction and turn ON. Another aspect concerning the proposed converter is that the input current exhibits a continuous behavior, which can be significant for various applications. The paper provides insights into the operational performance, steady state behavior, and mathematical underpinnings of the proposed dc-dc converter. Comparative evaluation of the static voltage gain of the proposed converter and other topologies with comparable characteristics will also be shown. Verification of the presented converter's key features are conducted through both simulation and experimental assessments using a 440-W laboratory prototype. Through these analyses, the efficacy and viability of the modified coupled-inductor SEPIC converter with enhanced voltage gain capability are confirmed.